E-Commerce Transaction System Core II (Product and Shop Management, Order Cancellation, Delivery Management, Vendor/Seller Management, Order Management): Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
E-commerce transaction system core II can disclose product information (such as quality,size, function, and so on) to assist the buyer in understanding the products. And they canadvertise their products online so that buyer can now see their products. Social media andother online platforms can now be a place where buyers and sellers meet. E-commerce mayprovide consumers with a streamlined purchasing experience and assist companies inreaching a larger market, eventually resulting in more sales and business expansion.As a result, the project team created a web-based E-Commerce system that automatestransactions; with web-based access to E-Commerce for the submission of relevant criteria aswell as verification and payment, orders and deliveries can now be conveniently tracked andprocessed by the E-Commerce Transaction System Core II. The system will includenumerous features requested by the customer that will assist researchers in convenientlymanaging research documents and other requirements.In this Research, E-commerce transaction system core II will offer the research community aconsolidated and efficient platform for managing research data and processes for E-Commerce, contributing to the expansion and development of research capabilities at BestlinkCollege of the Philippines. by making the research data and method more simple, the E-Commerce can focus more on conducting high-quality research and improving the quality ofproduct and customer services.
Keywords: IT & Management